A recessive Nav1.4 mutation underlies congenital myasthenic syndrome with periodic paralysis. (12th January 2016) - Habbout, Karima; Poulin, Hugo; Rivier, François; Giuliano, Serena; Sternberg, Damien; Fontaine, Bertrand; Eymard, Bruno; Morales, Raul Juntas; Echenne, Bernard; King, Louise; Hanna, Michael G.; Männikkö, Roope; et al.
Abstract : Objective: To determine the molecular basis of a complex phenotype of congenital muscle weakness observed in an isolated but consanguineous patient. Methods: The proband was evaluated clinically and neurophysiologically over a period of 15 years. Genetic testing of candidate genes was performed. Functional characterization of the candidate mutation was done in mammalian cell background using whole cell patch clamp technique. Results: The proband had fatigable muscle weakness characteristic of congenital myasthenic syndrome with acute and reversible attacks of most severe muscle weakness as observed in periodic paralysis. We identified a novel homozygous SCN4A mutation (p.R1454W) linked to this recessively inherited phenotype. The p.R1454W substitution induced an important enhancement of fast and slow inactivation, a slower recovery for these inactivated states, and a frequency-dependent regulation of Nav 1.4 channels in the heterologous expression system. Conclusion: We identified a novel loss-of-function mutation of Nav 1.4 that leads to a recessive phenotype combining clinical symptoms and signs of congenital myasthenic syndrome and periodic paralysis, probably by decreasing channel availability for muscle action potential genesis at the neuromuscular junction and propagation along the sarcolemma.